2017
DOI: 10.1038/s41598-017-09630-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Acute Kidney Injury to Chronic Kidney Disease Transition

Abstract: This study evaluated if there is a sexual dimorphism in the acute kidney injury (AKI) to chronic kidney disease (CKD) transition and the time-course of the potential mechanisms involved in the dimorphic response. Female and male rats were divided into sham-operated or underwent 45-min renal ischemia (F + IR, and M + IR). All groups were studied at 24-h and 1, 2, 3, or 4-months post-ischemia. Additionally, oophorectomized rats were divided into sham or IR groups. After 24-h, AKI extent was simllar in females an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 69 publications
3
43
1
Order By: Relevance
“…Females significantly upregulated FGF-21 and its co-receptor, b-Klotho, which controls energy expenditure, while male mice significantly upregulated SIRT-1 with potential renoprotective effects on lipid and glucose metabolism [35]. These sex differences in response to MetR diet may help explain the sexual dimorphism in the acute-to-chronic kidney disease transition [36]. …”
Section: Sex Differences In Response To Metr In Preclinical Modelsmentioning
confidence: 99%
“…Females significantly upregulated FGF-21 and its co-receptor, b-Klotho, which controls energy expenditure, while male mice significantly upregulated SIRT-1 with potential renoprotective effects on lipid and glucose metabolism [35]. These sex differences in response to MetR diet may help explain the sexual dimorphism in the acute-to-chronic kidney disease transition [36]. …”
Section: Sex Differences In Response To Metr In Preclinical Modelsmentioning
confidence: 99%
“…It has been reported that AKI is strongly associated with male gender and black race [12]. Several studies have been evaluated whether the risk of AKI, severity, and progression to CKD are influencing by sex but the results are conflicting [18,19]. A recent study found that males are 2.2 times more likely to develop AKI requiring renal replacement therapy [18], conversely another study found the women are more likely to have hospital-acquired AKI [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was observed that the female rats had a significant increase in mRNA levels of eNOS, TGF-β, and HIF-1α. A particularly interesting finding was the fact that female oophorectomized rats behaved similarly to male rats; in other words, this group developed CKD 44 . These results strongly suggest the participation of sex hormones in the transition from AKI to CKD.…”
Section: Sexual Dimorphism In the Aki To Ckd Transitionmentioning
confidence: 92%
“…Several years ago, it was thought that patients who survived an episode of AKI and who had a recovery of renal function would not have long-term consequences 31 . However, in recent years, this concept has changed based on several experimental and epidemiological studies demonstrating that AKI is a risk factor, leading to progressive kidney disease 7,[32][33][34][35][36][37][38][39][40][41][42][43][44] . In a recent meta-analysis that included 13 previously reported studies in patients who survived an AKI episode, the incidence of CKD and ESRD was 25.8% and 8.6%, respectively 34,35 .…”
Section: Mechanisms Involved In the Transition Of Aki To Ckdmentioning
confidence: 99%
See 1 more Smart Citation